Case Report: An ovarian epithelial-type serous adenocarcinoma of the testis was treated using systemic chemotherapy with bevacizumab, the treatment strategy used for ovarian serous carcinoma - Liu, Rui-Zhi; Zhang, Shuang; Gong, Jing; Yao, Jin; Zeng, Hao; He, Lang (Frontiers in Oncology, 2025)
Ovarian-type serous adenocarcinoma of the testis is an extremely rare malignant disease, and experience and evidence regarding its treatment are lacking. Herein, we describe the case of a 39-year-old man who presented with widespread metastasis in the retroperitoneal and pelvic lymph nodes after surgical resection of his right testicular tumor. Systemic chemotherapy with bevacizumab, the treatment strategy used for ovarian serous adenocarcinoma, was administered, and retroperitoneal lymph node dissection and radiotherapy followed after the lesions regressed. The patient has had over 3 years of progression-free survival. This is the first case of a bevacizumab combination in this disease and indicates that bevacizumab may be an option for the treatment strategy of this rare disease.